2019
DOI: 10.2147/cmar.s225739
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nomogram For The Prediction Of Malignancy In Small (8–20 mm) Indeterminate Solid Solitary Pulmonary Nodules In Chinese Populations</p>

Abstract: PurposeThis study aimed to develop and validate a nomogram for predicting the malignancy of small (8–20 mm) solid indeterminate solitary pulmonary nodules (SPNs) in a Chinese population by using routine clinical and computed tomography data.MethodsThe prediction model was developed using a retrospective cohort that comprised 493 consecutive patients with small indeterminate SPNs who were treated between December 2012 and December 2016. The model was independently validated using a second retrospective cohort c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
81
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(84 citation statements)
references
References 28 publications
0
81
1
Order By: Relevance
“…Only one study (17) included exposure to asbestos, none included exposure to radon or uranium, and only one (23) included passive exposure to tobacco smoke. Emphysema was collected in 2 studies (21,24) , and family history of lung cancer was collected in only one (21). Only one study (23) described peri ssural nodules, and two studies (23,26) included multiple nodules.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study (17) included exposure to asbestos, none included exposure to radon or uranium, and only one (23) included passive exposure to tobacco smoke. Emphysema was collected in 2 studies (21,24) , and family history of lung cancer was collected in only one (21). Only one study (23) described peri ssural nodules, and two studies (23,26) included multiple nodules.…”
Section: Resultsmentioning
confidence: 99%
“…30 Besides, another three models were also established for solid nodules based on a Chinese population (AUC=0.85~0.87). [31][32][33] Compared to these four models, the current solid-nodule models shared some similar risk factors, such as age, sex, history of malignancy, morphology, and serum CEA, but some novel markers like V25, RV/TLC, serum lymphocyte, CYFRA21-1, and NSE were also identified. As for model performance, these four were a little better than our models (AUC=0.82), which can be associated with some valuable predictors they enrolled, such as enhancement, VDT, as well as maximum uptake value of nodules.…”
Section: Discussionmentioning
confidence: 95%
“…28 Many prior studies have relied upon morphological findings such as the size, location, cavitation, calcification, spiculated sign and pleural indentation to accurately diagnose LNs. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In one prior large multi-center study, larger lesion size, evidence of spiculated sign and pleural indentation were all considered to be indicative of a higher risk of LN malignancy, whereas calcification was predictive of an LN being benign. 20 The reported diagnostic utility of CT-based spiculated sign varies significantly among prior studies and as such a meta-analysis is warranted in order to better understand the true diagnostic utility of this morphological parameter with F I G U R E 2 Methodological quality (A) graph and (B) summary greater statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to some benign LNs having been confirmed via CT follow-up in certain European studies, 8,14,21 whereas the majority of Chinese studies confirmed LN status via surgical resection. 9,12,13,[17][18][19][22][23][24][25] There are certain limitations to the present analysis. For one, all included studies were retrospective in nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation